- #1

- 2

- 0

solve for x:

1) 3x^2 - 2x +1=0

2) x^2 -4x + 20 = 0

3) (-2/x+1) + (3/1-x) = 7/x^2-1

and

find p(-2) if P(x) = 2x^4 - x^3 + 4x^2 + -8x + 3

again thx for any help :)

- Thread starter Sope0nARope
- Start date

- #1

- 2

- 0

solve for x:

1) 3x^2 - 2x +1=0

2) x^2 -4x + 20 = 0

3) (-2/x+1) + (3/1-x) = 7/x^2-1

and

find p(-2) if P(x) = 2x^4 - x^3 + 4x^2 + -8x + 3

again thx for any help :)

- #2

enigma

Staff Emeritus

Science Advisor

Gold Member

- 1,752

- 14

For the last one, substitute -2 in everywhere you see x, multiply and add them together.

If you post an attempt, we can help you a bit more.

- #3

- 2

- 0

x=2/3 + or - i root60/6 for the 1st 1

and x = 6,-2 for the 2nd i must be doing something wrong

- #4

enigma

Staff Emeritus

Science Advisor

Gold Member

- 1,752

- 14

For the third one, it looks like your parenthesis are a bit ambiguous.

(-2/x+1)

Is this (-2/x) +1 or -2/(x+1)?

Can you post your work, and we'll find the errors?

- Last Post

- Replies
- 8

- Views
- 1K

- Last Post

- Replies
- 11

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 1K

- Replies
- 2

- Views
- 4K

- Replies
- 33

- Views
- 4K

- Last Post

- Replies
- 3

- Views
- 7K

- Replies
- 4

- Views
- 1K

- Last Post

- Replies
- 4

- Views
- 1K

- Last Post

- Replies
- 9

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 1K